Label algorithm for the Maximum Flow problem - Perez Cupe, Rósulo (2002)
Presently work is studied the theorem of the flow maximum-cut minimum (L. Ford and D..Fulkerson) from the practical poin of view, this is its demonstration is based on the test of correctude of the algorithm of labels. The implementation of such an algorithm is also presented.